(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
Inclusive education also emphasizes the importance of collaboration among educators, parents, and support staff to ensure that each student’s unique needs are met. This may involve providing individualized support, assistive technology, and specialized instruction to help students with disabilities fully participate in classroom activities. Inclusive education also promotes a positive school culture that celebrates diversity and fosters a sense of belonging for all students. By embracing inclusive practices, primary schools can create an environment that nurtures the academic, social, and emotional growth of every student, regardless of their differences.